A deployment scenario: a taxonomy mapping and keyword searching for the application relation / Sharipah Setapa, Shahrol Hisham Baharom and Luke Jing Yuan - Setapa, Sharipah; Baharom, Shahrol Hisham; Luke, Jing Yuan (Universiti Teknologi MARA, Perlis, 2019)
Upgrading and patching is a method to strengthen the host and virtualisation devices from malware. In the deployment to different entity’s clients, different scenarios are faced to support their business process. A host and virtual machine (VM) is dependent on each other to provide high efficiency. A good design of virtual resources in a physical host can maintain the host’s efficiency. If the host is to be upgraded or patched, then the relationship with VM needs to be explored to avoid missing or malfunctioning of certain application on the host or VM. A relationship how to check whether the application scenario is working as expected is not being derived. This paper will discuss scenarios that we face and how it can be converted into taxonomy to provide a strategic approach when upgrading a specific item. With that, an analogy can be based on how the application scenario can be established as a model and converted into taxonomy for troubleshooting when execution is facing an error.